Serum interleukin-12 and interleukin-18 levels in patients with oesophageal squamous cell carcinoma - Diakowska, D.; Markocka-Mączka, K.; Grabowski, K.; Lewandowski, A. (Experimental Oncology, 2006)
Interleukin-12 (IL-12) and interleukin-18 (IL-18) play an important role as immunomodulatory factors in cancer pathogenesis. The aim of the study was analyze changes of serum IL-12 and IL-18 concentrations in oesophageal squamous cell carcinoma patients depending on the progression of cancer. Materials and Methods: Blood samples were taken from 41 patients with oesophageal cancer: 5 women and 36 men, mean age 59 ± 9 years. 23 patients had surgical resection of oesophagus with II and III tumor stage, 18 patients with IV stage of cancer progression were treated by palliative procedures. The control group included 15 healthy blood donors: 4 female and 11 males, mean age 41 ± 6 years. The concentrations of IL-12 and IL-18 were determined by ELISA tests. Results: Serum IL-12 and IL-18 amounts detected in blood of oesophageal cancer patients were significantly higher in comparison to control group (p < 0.001). Serum IL-12 level was higher in patients with IV stage of the disease than in patients with II and III stages. Also serum IL-18 level was significantly higher in patients with IV stage in comparison to patients surgically treated (p < 0.05). Statistically significant differences were found in concentrations of IL-18 according to clinicopathological parameters such as: stage of cancer progression, tumor depth, lymph node metastasis (p < 0.05). Conclusions: Serum IL-12 and IL-18 levels are significantly higher in oesophageal cancer patients than in the healthy subjects. A relation between IL-18 content and cancer progression has been registered.